Advancing acceptance: assessing acceptance of the ESR iGuide clinical decision support system for improved computed tomography test justification - Singer, Clara; Luxenburg, Osnat; Rosen, Shani; Vaknin, Sharona; Saban, Mor (Frontiers in Medicine, 2023)
Background: A clinical decision support system (CDSS), the European Society of Radiologists (ESR) iGuide, was developed to address gaps in the availability and use of effective imaging referral guidelines. Aim: This study aimed to assess the appropriateness of computed tomography (CT) exams with and without ESR iGuide use, as well as the usability and acceptance of the physician systems. Methods: A prospective single-center study was conducted in which data from 278 consecutive CT tests referred by physicians were collected in the first phase (T1), and physicians used the ESR iGuide system for imaging referrals in the second phase (T2; n=85). The appropriateness of imaging referrals in each phase was assessed by two experts, and physicians completed the System Usability Scale. Results: The mean appropriateness level on a scale of 0-9 was 6.62±2.69 at T1 and 7.88±1.4 at T2. When using a binary variable (0-6 = non-appropriate; 7-9 = appropriate), 70.14% of cases were found appropriate at T1 and 96.47% at T2. Physician specialty and status showed a higher likelihood of ordering an appropriate test (p=0.0011 and p=0.0192, respectively). However, the questionnaire results indicated low system trust and minimal clinical value, with all physicians indicating they would not recommend collegial use (100%). Conclusions: The study suggests that ESR iGuide can effectively guide the selection of appropriate imaging tests. However, physicians showed low system trust and use, indicating a need for further understanding of CDSS acceptance properties. Maximizing CDSS potential could result in crucial decision-support compliance and promotion of appropriate imaging.